PRINCIPLES OF RECLAMATION AND PHYTOMELIORATION OF DEVASTATED LANDSCAPES - Snitynskyi , В.; Ivankiv , М.; Kachmar , Н.; Datsko , Т.; Dydiv , А.; Horodyska , І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
The article presents an analysis and synthesis of literature sources, as well as the results of the author's research on the evaluation of technological and organizational solutions for revitalizing technogenic landscapes. It focuses on the large areas of devastated lands in Ukraine that were formed due to various types of economic activities, resulting in the destruction of natural ecosystems. These lands need to be restored. The conditions of technogenesis have caused transformations of the life of flora, particularly in the affected areas, explaining and assisting which encounters complex theoretical problems. These issues require new principles and methods to optimize the damaged landscapes using phytomelioration, phytoreclamation, and environmental protection measures, which is an essential task for general environmental conservation. Implementing modern revitalization methods will restore disturbed lands, ensure their rational use, recover soil fertility and biodiversity in disturbed landscapes, and create new economic development opportunities. This, in turn, will improve the environment and the quality of human life. The purpose of this work is to justify the need to develop a set of solutions for organizing a phased planning of the rational use of disturbed lands. Ukraine has a variety of natural conditions, so the choice of plant species for creating stable phytocenoses during reclamation should be justified and ecologically and phytocenotic compatible and suitable for local conditions. To be successful, the process of revitalizing technogenically transformed landscapes should be based on the use of potential opportunities and trends inherent in nature itself. Based on the analysis of scientific literature on the rational use of disturbed lands to adapt them to repeated and prospective use, the article highlights that lands formed as a result of human technogenic activity can be used for recreation and various economic development.